The Research on Dedicated-path Protection Methods in Elastic Optical Networks with Data Centers - Xiao-dong FU; Yao-pan WANG; Yi-chun SHEN; Hong-lian FANG; Bo-wen CHEN (Guangtongxin yanjiu, 2022)
With the development of big data, cloud services, and artificial intelligence, the optical network is developing towards scale and complexity, which suffers from larger probability of network failure. It is necessary to provide dedicated-path protection for each connection request to reduce the loss caused by the network failures. Therefore, in order to guarantee the network survivability, we propose a dedicated-path protection optimization method to improve the network resource efficiency in elastic optical networks with data centers. The simulation results show that the proposed dedicated-path protection optimization method can effectively reduce the blocking probability, improve the network resource utilization, and solve the survivability problem of elastic optical networks in data centers.